ASSESSMENT OF HEAVY METAL CONTAMINATION AT WEST AND EAST COASTAL AREA OF PENINSULAR MALAYSIA - Redzwan, Ghufran; Abdul Halim, Hafizah; Alias, Siti Aisah; Rahman, M. Motior (Malaysian Journal of Science, 2014)
Five heavy metal elements [Pb (II), Cr (VI), Ni (II), Zn (II) and Cu (II)] in the sediment of the two coastal areas had been analyzed of the Mideast and Midwest of Peninsular Malaysia in the year of 2012. This is to assess and monitor contamination of heavy metal at a mangrove area in the state of Negeri Sembilan, Melaka and Pahang. Overall and individual analyses of the heavy metals showed the concentration of the named heavy metals were not at alarming stage. All analyzed elements were found to be much lower than the international guideline provided by the Chinese (EPA-China), Canadian (CEPA) and American (US-EPA). Quantitative assessment using Enrichment Factor shows that all analyses elements were to found be within the degree of background concentration. Keywords: Enrichment factor, Port Dickson, Kuantan, South China Sea, Strait of Malacca, Mangrove Forest Area